(untitled) (Humanis, 2026)
This research aims to examine elements of Javanese culture in the novel "Garuda Gaganeswara Teka-Teki Jalan Lurus Melingkar" (GGTTJLM) using the Koentjraningrat Literary Anthropology approach. As a country rich in cultural diversity, Indonesia holds a rich culture that is the heritage of its people. However, the potential for social divisions can arise if this diversity is not properly understood and monitored. Children’s literature, as depicted in Nilandari’s work entitled "Garuda Gaganeswara: The Puzzle of a Straight and Circular Road", plays an important role in shaping, reflecting and inheriting the values, norms and traditions of society. The results of the research show that the representation of Javanese culture in the novel GGTTJLM reflects local wisdom, the identified cultural elements involve community activities in language, knowledge systems, social organizations, living equipment and technology systems, livelihoods, religion and art.